Evaluation of Pterygoid Muscles in Patients with Temporomandibular Disorders (Medical Forum Monthly, 2023)
Objective: To evaluate pterygoid muscles in patients with temporomandibular disorders.Study Design: Descriptive Cross-sectional study.Place and Duration of Study: This study was conducted at the Nishtar Institute of Dentistry, Multan from April 2021 to March 2022 in one year duration.Materials and Methods: Total 100 subjects were selected for the study purpose including 40%, 17%, 15%, 16% and 12% from prosthodontics, oral and maxillofacial surgery, operative dentistry, orthodontics, and general dentistry respectively. A survey was administered to one hundred dentists representing five dental specialties in district Multan, including both dental institutes and private practices. The survey questionnaire was to assess dentists' preferred methods for evaluating the medial pterygoid, inferior lateral pterygoid, superior lateral pterygoid, masseter, and temporalis muscles.Results: When evaluating the superior and inferior lateral pterygoid muscles, the majority of dentists (54% and 60% respectively) preferred using the combination of palpation and functional manipulation method, which is consistent with the published literature. A minority of participants chose digital palpation as their preferred method for assessing the lateral pterygoid muscles. When it came to evaluating the medial pterygoid muscles, 59% of the dentists favored a combination of techniques, while 22% endorsed relying solely on functional manipulation.Conclusion: The study's limitations lead to several notable conclusions. Firstly, a significant number of local dentists demonstrate a preference for utilizing digital palpation when assessing the masseter and temporalis muscles during TMJ examinations. Conversely, when it comes to evaluating the pterygoid muscles, the majority of local dentists tend to employ a combination of palpation and functional manipulation techniques. Nevertheless, it is essential to carry out additional research to thoroughly assess the diagnostic approaches utilized by dentists in the local context and compare them with universally established standards.